Iranian undergraduate non-English majors’ interpretation of english structures - Azam Noora, (Penerbitan UKM, 2009)
The present study sought to determine whether Iranian non-English major students with or without the experience of attending language institutes, were more influenced by the type of verb or the argument structure patterns in their interpretation of English structures. To answer this question, 100 non-English major participants took part in a grouping task which was designed to reveal the participants' preference in sentence interpretation. Except for those who did not have the required knowledge base and displayed no grouping preference, the participants of the study exhibited three different grouping or sorting strategies in their performance: verb-centered strategy and two types of construction-based performance. The results of a Chi square test indicated that regardless of attending language institutes, the said participants were more inclined to group the structures (i.e., through interpreting them) by relying on the structures' verb types rather than paying attention to the argument structure patterns around which the structures were configured.The implication of these findings is that at least in a foreign language context, a verb valency-based reading strategy is needed to enhance the foreign language learners’ information processing skills. The pedagogical overtones of the findings would affect both teaching activities as well as syllabus design and material development for non- English majors’ English books used in the university